О ПРОСТРАНСТВЕННО-ВРЕМЕННОЙ ОНТОЛОГИИ ТЕОРЕТИЧЕСКОЙ ФИЗИКИ - Будко, В. В. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 1970)
С позиции диалектического определения свойства сопоставлены субстанциализм ирелятивизм в понимании пространства и времени, рассмотрены допустимость собственныхпространств, лишенных пространственного фона. Обсуждена гносеологическая природанетрёхмерных пространств и допространственно-временных объектов.В. В. БудкоПРО ПРОСТІР І ЧАС В ОНТОЛОГІЇ ТЕОРЕТИЧНІЙ ФІЗИЦІЗ позиції діалектичного визначення властивості співвіднесені субстанціалізм тареляціонізм у розумінні простору та часу, розглянута припустимість власних просторів безпросторового фону. Обговорена гносеологічна природа нетрьохвимірних просторів тадопросторово-часових об’эктів.Ключові слова: властивість, субстанціалізм, реляціонізм, простір, власний простір,фоновий простір, первинні об’єкти.V. BudkoABOUT SPACE-TIME ONTOLOGY OF THEORETICAL PHYSICSThe opposition of substancialism and relationism in space-time cognition is discussed from theposition of dialectical definition of property. It is considered the assumption of background independencethat is deprived of spatial background. Gnosiological nature of non-three-dimensional spaces, unspatialand untemporal objects is verified in the article.Key words: property, substancialism, relationism, background independence, background space,primary objects.